HUBUNGAN PENGETAHUAN KELUARGA TENTANG BPJS (BADAN PENYELENGGARA JAMINAN SOSIAL) DENGAN PERILAKU KELUARGA DALAM MENGIKUTI PROGRAM BPJS - Indah Rohmawati (coba, 2018)
Abstract Everyone is entitled to an adequate standard of living for the health and well-being of himself and his family including the right to food, clothing, housing and health care. In addition, everyone also has the obligation to participate in social health insurance program through BPJS (Social Security Administering Body). Although the government regulation has been set still still find a family that has not become a participant BPJS Health. Many factors that can influence the behavior in following the BPJS program include knowledge of BPJS. The purpose of the research is to prove the relationship of family knowledge about BPJS (Social Security Administering Body) with family behavior in following BPJS program. Type of analytic research with cross sectional design and conducted for 1 year. Population All families in RT 001 RW 001 Tenggarejo Village Tanggunggunung District Tulungagung Regency, with total sampling technique obtained 78 respondents. Data were collected by using a knowledge questionnaire about BPJS and behavioral questionnaires in the BPJS program. Data analysis technique using Chi-Square test and got the result p value of 0.009 means there is a relationship between the knowledge of respondents about BPJS with respondents' behavior in following the BPJS program, this is because the lack of knowledge about BPJS can cause not have a solid basis to create new behavior and tend not to follow the new behavior or in this case do not follow BPJS program